2015
DOI: 10.3906/bot-1401-10
|View full text |Cite
|
Sign up to set email alerts
|

A conspectus of Scorzonera s.l. in Turkey

Abstract: The genus Scorzonera L. (Asteraceae), with about 160 species belonging to the subtribe Scorzonerinae Dumort. of the tribe Cichorieae, is widespread in the more arid regions of Eurasia and northern Africa (Bremer and Anderberg, 1994;Nazarova, 1997).After the genus Scorzonera s.str. was revised by Chamberlain (1975) for the Flora of Turkey, many new species have been recorded from Turkey. The classification of the genus has been highly controversial (Nazarova, 1997;Mavrodiev et al., 2004), and because of this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 14 publications
4
27
0
Order By: Relevance
“…Pseudopodosper mum. This taxonomic concept is in accordance with the following studies: Lipschitz (1964), Rechinger (1977), Safavi (2013), and Coşkunçelebı & al. (2015).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Pseudopodosper mum. This taxonomic concept is in accordance with the following studies: Lipschitz (1964), Rechinger (1977), Safavi (2013), and Coşkunçelebı & al. (2015).…”
Section: Introductionsupporting
confidence: 87%
“…2009a. Instead of splitting Scorzonera into different genera, some workers (Lipschitz 1964;Rechinger 1977;Safavi 2013;Coşkunçelebı & al. 2015) recognized three subgenera: S. subg.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to this revisional study, S. inaequiscapa (x = 7) and S. semicana (x = 7) should also be transferred under the subgenus Pseudopodospermum (x = 7). The basic chromosome numbers of these 2 taxa also support the transfer of the last 2 taxa under the subgenus Pseudopodospermum (Coşkunçelebi et al, 2015). In our study, chromosome numbers of 32 Scorzonera taxa were reported.…”
Section: Discussionmentioning
confidence: 73%
“…Coşkunçelebi et al (2015) reported that S. hieraciifolia (x = 7) should be transferred to subgenus Podospermum (x = 7), based on morphological, anatomical, and other studies. Chromosome number is in accordance with the basic chromosome number of Podospermum and thus supports this opinion.…”
Section: Discussionmentioning
confidence: 99%
“…C. bozkirensis is different from C. cephalotes by its stem indumentum arachnoid with a few multicellular hairs to tomentose hairs (not many multicellular hairs) ( Figures 4A, 4B, 4D, and 4E) and it differs from C. pugnax by its stems densely arachnoid to tomentose with a few multicellular hairs (not only sparsely arachnoid) ( Figures 4B 4C, 4E, and 4F). Furthermore, the setae on the leaf are different in terms of density ( Figures 5A-5F) The morphological characters of the cypsela are quite useful for the delimitation of different taxa at both the generic and species level within the genera of Asteraceae, such as Scorzonera L., Lactuca L., Cicerbita Wallr., Prenanthes L., Achillea L., and Carduus L. (Akçin and Akçin, 2014;Köstekçi and Arabacı, 2014;Abid and Qaiser, 2015;Coşkunçelebi et al, 2015Coşkunçelebi et al, , 2016Aytaç et al, 2016). In addition, the macro-and micromorphological features of the cypselae of Cirsium taxa can be used as distinguishing characteristics.…”
Section: (S Of Turkey) Bozkirensismentioning
confidence: 99%